A retrospective look at the artificial insemination in sheep - Hinojosa Benavides, René Antonio (2019)
The aim was to analyze the effect that this reproductive biotechnology on the production of sheep, mainly on fundamental aspects such as the reproductive efficiency, the genetic improvement, the technology transfer to the field and training of the producer, everything finally reflected in the productivity and the profitability of sheep production, taking into account also all the factors that affect the correct development of artificial insemination, avoiding the moments of more heat or environmental cold and practicing the flushing if the general state of the She advises it. It was concluded that the differences between the results obtained by the different farms are highly significant.